YAP/TAZ and EZH2 synergize to impair tumor suppressor activity of TGFBR2 in non-small cell lung cancer. (1st March 2021) - Lo Sardo, Federica; Pulito, Claudio; Sacconi, Andrea; Korita, Etleva; Sudol, Marius; Strano, Sabrina; Blandino, Giovanni
Abstract: Lung cancer is the leading cause of cancer-related deaths, worldwide. Non–small cell lung cancer (NSCLC) is the most prevalent lung cancer subtype. YAP and TAZ have been implicated in lung cancer by acting as transcriptional co-activators of oncogenes or as transcriptional co-repressors of tumor suppressor genes. Previously we reported that YAP and TAZ regulate microRNAs expression in NSCLC. Among the set of regulated miRNAs, the oncogenic miR-25, 93, and 106b, clustering within the MCM7 gene were selected for further studies. We firstly identified Transforming Growth Factor-β (TGF-β) Receptor 2 (TGFBR2), a member of the TGF-β signaling, as a target of the miRNA cluster, which exhibited prognostic value because of its tumor suppressor activity. We found that YAP/TAZ-mediated repression of TGFBR2 occurs both: post-transcriptionally through the miR-106b-25 cluster and transcriptionally by engaging the EZH2 epigenetic repressor that we reported here as a novel target gene of YAP/TAZ. Furthermore, we document that YAP/TAZ and EZH2 cooperate in lung tumorigenesis by transcriptionally repressing a specific subset of tumor suppressor genes, including TGFBR2. Our findings point to YAP/TAZ and EZH2 as potential therapeutic targets for NSCLC treatment. Highlights: YAP/TAZ post-transcriptionally inhibit TGFBR2 through the oncogenic miR 25/93/106b. YAP and TAZ transcriptionally regulate the epigenetic repressor EZH2. YAP/TAZ and EZH2 transcriptionally co-repress oncosuppressor genes, including TGFBR2. Inhibition of YAP/TAZ and EZH2 re-activates oncosuppressor genes in NSCLC. Combined inhibition of YAP/TAZ and EZH2 is a potential therapeutic strategy in NSCLC.